Best practices for datacom facility energy efficiency. (American Society of Heating, Refrigerating, and Air-Conditioning Engineers, 2009)
"The intent of this publication is to provide the reader with detailed information on the design of datacom facilities that will aid in minimizing the life-cycle cost to the client and to maximize energy efficiency in a facility to align with ASHRAE's stated direction to lead the advancement of sustainable building design and operations"--Provided by publisher.
Keywords: Data processing service centers -- Design and construction.; Electronic data processing departments -- Equipment and supplies -- Protection.; Buildings -- Environmental engineering.; Data processing service centers -- Energy conservation.; Data processing service centers -- Cost of operation.; elektronické knihy; electronic books